In Vitro Activity of Iclaprim Against Methicillin-Resistant Staphylococcus aureus Nonsusceptible to Daptomycin, Linezolid or Vancomycin - B Huang, David; Hawser, Stephen; G. Gemmell, Curtis; F. Sahm, Daniel (Journal of Drug Resistant Pathogen Research, 2017)
Iclaprim is a novel bacterial dihydrofolate reductase inhibitor in Phase 3 clinical development for the treatment of acute bacterial skin and skin structure infections and hospital acquired bacterial pneumonia caused by Gram-positve bacteria. Daptomycin, linezolid and vancomycin are commonly used antibiotic for these indications. With increase selective pressure to these generic antibiotics, outbreaks of bacterial resistance to these antibiotics have been reported. This in vitro study evaluated the activity of iclaprim against methicillin-resistant Staphylococcus aureus (MRSA) isolates, which were also not susceptible to daptomycin, linezolid or vancomycin. Iclaprim had an MIC ≤1 µg/ml to the majority of MRSA isolates that were nonsusceptible to daptomycin (5 of 7 71.4%), linezolid (26 of 26 100%), or vancomycin (19 of 28 66.7%). In time-kill curves analyses, iclaprim demonstrated ≥3 log10 reduction in CFU/mL at 4-8 hours for tested strains and isolates nonsusceptible to linezolid or vancomycin. Together these data support the use of iclaprim in serious infections caused by MRSA nonsusceptible to daptomycin, linezolid or vancomycin.
Keywords: iclaprim; daptomycin; linezolid; vancomycin; MRSA